Libraries in Finland Establish Consortia - Häkli, Esko (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2001)
I will discuss the development of organized consortia, which are based on a charter or a written contract. I will also deal with some issues related to the organization of the consortia. I would already here like to stress, that if a consortium wants to achieve results it, in addition to a charter or a contract, also needs an executive body that carries out the work and makes sure that the plans and decisions are not only prepared but also put into practice. One of the main weaknesses of many cooperative arrangements between libraries has been the absence of a common executive not only taking care of the practicalities but also safeguarding the continuity. A committee can never fulfill the tasks of an executive body because running a consortium successfully requires much more effort than what is normally anticipated. In Finland the National Library has been given the task to enhance the cooperation between the research libraries of the country and to support their consortia . According to the National Library Strategy (adopted in November 1999) the Library is functioning as a common resource of the country’s research libraries. In this capacity it has been instrumental in creating the comprehensive consortia described below and is also responsible for running their daily business. It is possible that an arrangement of this kind is more typical for a small country than for a bigger one.